Relationship between Motivation and Type II Diabetes Mellitus Dietary Compliance - Nashrullah, Rofiq Farhi; Ari, Nugroho; Wijaya, Siswanto Agung; Adyani, Asta (MAGNA MEDICA Berkala Ilmiah Kedokteran dan Kesehatan, 2021)
Background: Diet is a habit about the amount and type of food and drinks an individual consumes from day to day, especially foods designed to improve specific individual needs, including or excluding certain foods. Diet regulation is the regulation of the type and amount of food with specific purposes such as maintaining health and nutritional status and helping to cure disease, every diet includes food, but not all foods are included in the diet category. In a diet, the type and amount of food are determined and controlled to achieve individual goals. The diabetic diet is a diet that is recommended for people with diabetes, usually limited in sugar or easily absorbed carbohydrates. In addition to regularly controlling sugar levels, having a regular diet and exercise is the key to successful diabetes management.Objective: To explore the relationship between motivation and dietary compliance with type 2 diabetes mellitus in diabetes mellitus patients in Galis village, Galis Health Center, Pamekasan District.Method: Observational research with cross-sectional research designResults: Most of the type 2 diabetes mellitus sufferers experienced high motivation. Most of the type 2 diabetes mellitus sufferers comply with the type 2 diabetes mellitus diet.Conclusion: There is a relationship between motivation and adherence to type 2 diabetes mellitus.